Antimicrobial Peptides in Gastrointestinal Inflammation - Simon Jäger; Eduard F. Stange; Jan Wehkamp (International Journal of Inflammation)
Acute and chronic inflammations of mucosal surfaces are complex events in which the effector mechanisms of innate and adaptive immune systems interact with pathogenic and commensal bacteria. The role of constitutive and inducible antimicrobial peptides in intestinal inflammation has been investigated thoroughly over the recent years, and their involvement in various disease states is expanded ever more. Especially in the intestines, a critical balance between luminal bacteria and the antimicrobial peptides is essential, and a breakdown in barrier function by impaired production of defensins is already implicated in Crohn's disease. In this paper, we focus on the role of antimicrobial peptides in inflammatory processes along the gastrointestinal tract, while considering the resident and pathogenic flora encountered at the specific sites. The role of antimicrobial peptides in the primary events of inflammatory bowel diseases receives special attention.